2020
DOI: 10.1016/j.envpol.2019.113865
|View full text |Cite
|
Sign up to set email alerts
|

Identification of microplastics in surface water and Australian freshwater shrimp Paratya australiensis in Victoria, Australia

Abstract: Compared to marine microplastics research, few studies have bio-monitored microplastics in inland waters. It is also important to understand the microplastics' uptake and their potential risks to freshwater species. The Australian glass shrimp Paratya australiensis (Family: Atyidae) is commonly found in fresh waterbodies in eastern Australia, and are sensitive to anthropogenic stressors but have a wide tolerance range to the natural environmental conditions. This study aimed to understand the microplastics' oc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
58
2
7

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 174 publications
(72 citation statements)
references
References 49 publications
5
58
2
7
Order By: Relevance
“…Microplastics were also extensively monitored in shellfish, such as blue mussels, shrimps, and clams [ 11 , 20 , 40 , 45 , 52 , 59 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 , 85 , 86 , 87 , 88 , 89 , 90 , 91 , 92 , 93 , 94 , 95 , 96 , 97 , 98 , 99 ] ( Table 3 ). Unlike fish, soft tissues were dissected and digested to separate microplastics in mussels, clams, and oysters.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Microplastics were also extensively monitored in shellfish, such as blue mussels, shrimps, and clams [ 11 , 20 , 40 , 45 , 52 , 59 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 , 85 , 86 , 87 , 88 , 89 , 90 , 91 , 92 , 93 , 94 , 95 , 96 , 97 , 98 , 99 ] ( Table 3 ). Unlike fish, soft tissues were dissected and digested to separate microplastics in mussels, clams, and oysters.…”
Section: Resultsmentioning
confidence: 99%
“… Fractions of plastic materials identified in seafood and salt. Data from References [ 11 , 14 , 15 , 21 , 24 , 29 , 30 , 34 , 39 , 40 , 45 , 47 , 48 , 50 , 51 , 52 , 62 , 71 , 74 , 75 , 76 , 77 , 78 , 80 , 81 , 86 , 90 , 91 , 95 , 96 , 98 , 99 ]. (PE: polyethylene, PP: polypropylene, PS: polystyrene, PET: polyethylene terephthalate, PA: polyacrylate).…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…The lack of environmental protection measures may explain why rural areas were more polluted than urban areas in Lake Dongting (China) [59]. Similarly, microplastic pollution in Australia is widespread in rural and urban areas, with no differences in concentrations between samples from different sites [60]. Therefore, the absence of effective measures to prevent entry of fMPs into freshwater systems is a relevant factor to be considered when modelling plastic inputs.…”
Section: Factors Influencing Fmp Contaminationmentioning
confidence: 99%
“…Pellets were not characterised in this study. Previous research has found that they were polyethylene (PE) microbeads used in personal care products, cleaning compounds and industrial sandblasting [17,40].…”
Section: Microplastic Size Distributionmentioning
confidence: 99%